Penerapan Balanced Scorecard Untuk Menilai Kinerja Pada Koperasi Karyawan PT. Kedawung Setia Industrial, Tbk - Nala Hikmatul Machmudah; Slamet Riyadi (Jurnal Akuntan Publik, 2025)
The purpose of this study is to evaluate the implementation of Balanced Scorecard (BSC) as a performance management tool in the Employee Cooperative of PT Kedawung Setia Industrial, Tbk. Qualitative research methods were used with interviews, questionnaires, observation, and document analysis as data collection techniques. The application of BSC in the Employee Cooperative of PT Kedawung Setia Industrial, Tbk helps measure and monitor overall performance, ensuring that financial, customer, internal business, and learning and growth perspectives become the main focus. The results showed that the performance of the Employee Cooperative of PT Kedawung Setia Industrial, Tbk, when viewed through the four perspectives of the Balanced Scorecard, can be categorized as quite good. The active involvement of the management, members, and related parties in the implementation of BSC is the key to success in improving the performance of the PT Kedawung Setia Industrial, Tbk Employee Cooperative. This research contributes to the understanding of the concept of performance management in the context of cooperatives and provides a basis for further development in improving the effectiveness of cooperative performance management. The findings of this study have practical and theoretical implications that can help decision makers in cooperatives and researchers in the field of cooperative management.